Apraxia: Definition, clinical contexts, neurobiological profiles and clinical treatments - Perrotta, Giulio (Global Journal of Medical and Clinical Case Reports, 2020)
Starting from the general concept of Apraxia, the present work focuses on the clinical, neurobiological, and functional aspects of the morbid condition, suggesting a multidimensional treatment between rehabilitation exercises for lost skills and psychotherapy.